The Association Rules of Factors on Customer Choices of Accommodation: Pak Chong, Nakhon Ratchasima - Visadsoontornsakul, Punyavee (Dusit Thani College Journal, 2020)
Accommodation plays a crucial role in facilitating visitors when they are traveling. It can be noticed that the hotel is the main factor which affects a lot on visitors’ decisions. If any tourist attractions are not able to provide good accommodation, it will decrease the number of visitors who would travel and spend the nights. Thus, to indicate the factors which affect customer choices on accommodation. The research had been conducted based on the 452 online surveys targeting the tourists who spent more than one night in Pak Chong area, Nakhon Ratchasima province. A Qualitative research method, the association rules, investigates the relationship of factors which consists of the personal information and some improvement factors; Accommodation, Attraction, Activities, Amenities, and Accessibility. The research objective is to provide accommodation improvement guidance which concluded from the rules of the association for increasing the number of visitors in the Pak Chong area. The outcome suggests the effective accommodation should provide interesting activities such as paintball, rafting, biking and other facilities such as free internet connection, free transportation to the hotel. The cleanness, well-prepared decoration, and safety of accommodation is an important factor that should keep in consideration firstly. In summary, all mentioned factors are the main factors that directly affect the customer choices.